Female rose bitterling prefer MHC-dissimilar males: experimental evidence - Reichard, Martin; Spence, Rowena; Bryjová, Anna; Bryja, Josef; Smith, Carl (PloS one, 2012)
The role of genetic benefits in female mate choice remains a controversial aspect of sexual selection theory. In contrast to "good allele" models of sexual selection, "compatible allele" models of mate choice predict that females prefer mates with alleles complementary to their own rather than conferring additive effects. While correlative results suggest complementary genetic effects to be plausible, direct experimental evidence is scarce. A previous study on the Chinese rose bitterling (Rhodeus ocellatus) demonstrated a positive correlation between female mate choice, offspring growth and survival, and the functional dissimilarity between the Major Histocompatibility Complex (MHC) alleles of males and females. Here we directly tested whether females used cues associated with MHC genes to select genetically compatible males in an experimental framework. By sequentially pairing females with MHC similar and dissimilar males, based on a priori known MHC profiles, we showed that females discriminated between similar and dissimilar males and deposited significantly more eggs with MHC dissimilar males. Notably, the degree of dissimilarity was an important factor for female decision to mate, possibly indicating a potential threshold value of dissimilarity for decision making, or of an indirect effect of the MHC.
Keywords: Mating Preference, Animal; lineární modely; Decision Making; hlavní histokompatibilní komplex; výběrové chování; Choice Behavior; Female; Animals; rozhodování; ženské pohlaví; mužské pohlaví; Male; Major Histocompatibility Complex; zvířata; Linear Models; sexuální výběr u zvířat; Cyprinidae